Estimating the Social Profitability of India's Rural Roads Program A Bumpy Ride - Bell, Clive (The World Bank, 2012)
India's rural roads program, Pradhan Mantri Gram Sadak Yojana, aims to draw villagers into the mainstream by improving not only their terms of trade, but also their educational attainments and health. Treating each all-weather feeder road as an isolated element within the larger network, and using shadow prices to value the main components of costs and benefits, the paper demonstrates that further investments in the program are, with high probability, socially profitable, especially in poorer and more densely settled regions. Taking the entire set of new individual roads together, qualitative arguments suggest that their external and spill-over effects on the system as a whole probably generate some net additional benefits, but of very uncertain magnitude